A Navigation Lamp Detection to Avoid Collision for Unmanned Surface Vehicle (USV) - Putu Indah Sri Puspadewi; Tsaubiyah Khairun Nisa Ali; Nurdiansari, Henna; Akhmad Kasan Gupron; Akhmad Rizqi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
Unmanned Surface Vehicle (USV) or unmanned ship has become a major focus in the development of shipping technology to improve the efficiency and safety of navigation on the water. This research carried out the design and creation of an unmanned ship system equipped with an ESP32 camera to detect the navigation lights of other ships and avoid potential collisions. In this system, the initial response of the ESP32CAM camera reads the color of the lights approaching the unmanned ship with less than 100 cm. ESP32CAM reads and identifies colors through image processing. When ESP32CAM detects green and red-light colors, the ESP32CAM microcontroller commands the buzzer to sound. The color detection system works with this command, if ESP32CAM detects red then the ESP32CAM microcontroller will send a signal to the servo motor to move left, while ESP32CAM detects green the ESP32CAM microcontroller will send a signal to the servo motor to move right. The servo motor functions as a ship rudder drive of a USV or unmanned ship. The Navigation lamp system test using ESP32CAM camera to prevent ship collisions is carried out with a predetermined scenario, independent light color testing, and whole system testing. The results of the research are : Color detection is successful. The camera can recognize the color of the light and the unmanned ship is able to take appropriate action to avoid collisions based on the color light signal and the navigation lamp system. The ESP32CAM camera can identify the optimum light at 100cm.